2021
DOI: 10.1177/17085381211032756
|View full text |Cite
|
Sign up to set email alerts
|

The roles of immune cells in atherosclerotic calcification

Abstract: Atherosclerosis is the leading cause of acute cardiovascular events, and vascular calcification is an important pathological phenomenon in atherosclerosis. Recently, many studies have shown that immune cells are closely associated with the development of atherosclerosis and calcification, but there are many conflicting viewpoints because of immune system complications, such as the pro-atherosclerotic and atheroprotective effects of regulatory B cells (Bregs), T helper type 2 (Th2) cells and T helper type 17 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 136 publications
(163 reference statements)
0
1
0
Order By: Relevance
“…VC is a chronic inflammatory disease that is closely related to the abnormal activation of macrophages, B cells, T cells, and other immune cells 17 . We previously confirmed that peripheral macrophages in T2D patients are prone to polarize into the M1 phenotype and secrete inflammatory factors and extracellular vesicles to promote VC 18–20 .…”
Section: Introductionmentioning
confidence: 64%
“…VC is a chronic inflammatory disease that is closely related to the abnormal activation of macrophages, B cells, T cells, and other immune cells 17 . We previously confirmed that peripheral macrophages in T2D patients are prone to polarize into the M1 phenotype and secrete inflammatory factors and extracellular vesicles to promote VC 18–20 .…”
Section: Introductionmentioning
confidence: 64%